Pengaruh Model Pembelajaran Talking Stick dan Motivasi Berprestasi terhadap Hasil Belajar IPS Siswa Kelas VIII SMP Negeri 1 Pematang Siantar T.A 2022/2023 - Susy Alestriani Sibagariang; Benjamin Albert Simamora; Apriana Panggabean (LP. Ma'arif Janggan Magetan, 2022)
This study aims to analyze the effect of the talking stick learning model and achievement motivation on social studies learning outcomes for class VIII students. This research method uses the experimental method. Data collection techniques using tests, questionnaires, and documentation. A sample of 64 respondents was taken from a total population of 351 students of SMP Negeri 1 Pematang Siantar. The data analysis technique used normality test, hypothesis testing with multiple linear regression analysis and t test and F test. The results showed that the talking stick learning model and achievement motivation had a positive and significant influence on students' social studies learning outcomes.